Body mass index and self-perception of overweight and obesity in rural, urban and rural-to-urban migrants: PERU MIGRANT study. - Christian Loret de Mola; Timesh D Pillay; Francisco Diez-Canseco; Robert H Gilman; Liam Smeeth; J Jaime Miranda (PLoS ONE)
Objective This study aimed to compare self-reported weight and body mass index (BMI) in order to determine discrepancies between subjective and objective obesity-related markers, and possible explanatory factors of overweight and obesity underestimation, in urban, rural and migrant populations. Materials and methods Data from the PERU MIGRANT study, a cross-sectional study, in low-income settings, of urban, migrant (rural-to-urban), and rural groups, including BMI, self-reported weight and socio-demographic indicators were analyzed. Percentage of concurrences between BMI and self-reported weight and Kappa coefficients for inter-rater agreement were calculated. Univariate and standardized descriptive analyses were performed to identify potential explanatory variables for weight underestimation in only overweight and obese individuals, using established BMI and waist circumference cut offs. Results 983 Participants-199 urban, 583 migrants and 201 rural-were analyzed. Based on BMI, overall prevalence of obesity was 20.1% (95% CI 17.6%-22.6%), and overweight was 38.3% (95% CI 35.2%-41.2%), with differences between study groups (p<0.001). Only 43% of the whole sample had matching self-reported weight and BMI status, whereas 54% underestimated and 3% overestimated their BMI category. Kappa coefficient, between BMI and self-reported weight, for the entire sample was 0.16, rural residents had the lowest coefficient (0.01) and the most underestimation, especially in the overweight category. In overweight and obese individuals, deprivation index (p = 0.016), age (p = 0.014) and waist circumference (p<0.001) were associated with weight underestimation. Discussion Overall, high levels of overweight, obesity, and underestimation of BMI status were found, with poor agreement between BMI and self-reported weight, showing the unawareness of weight status severity in this low-income setting.